Chemical Composition and Repellent Activity of the Essential Oil of Ocimum minimum L. on Drosophila Species - Celik Onar, H.; Hasdemir, B.; Yusufoglu, A. (Asian Journal of Chemistry, 2010)
The chemical composition of the essential oil of Ocimum minimum L. from Istanbul, Turkey was investigated and repellent activity against Drosophila species were examined. Ocimum minimum L. grown in Istanbul with its high content of linalool (36-41 %) showed a good repellency.